Pollution affects even oceanic marine protected areas in Southwestern Atlantic - Mello, Thayná J.; Longhini, Cybelle M.; Wanderley, Bruno Mattos Silva; Silva, Cesar Alexandro da; Lehrback, Bethânia Dal'Col; Bom, Fábio Cavalca; Neto, Renato Rodrigues; Sá, Fabian; Vieira, Edson A.; Costa, Vladmir E. [UNESP]; Longo, Guilherme O. (Elsevier, 2025)
Reefs are facing a global decline with sewage pollution emerging as a significant and poorly understood threat. Inadequate wastewater management and disorderly urbanization contribute to water pollution globally. Tropical Southwestern Atlantic comprises a set of oceanic Marine Protected Areas (MPAs) including the Fernando de Noronha Archipelago in Brazil, which has experienced significant population growth without expanding the sewage infrastructure. We mapped and quantified marine pollution in these MPAs, characterizing pollution sources and evaluating their effects on benthic and fish communities in 13 reef sites. We quantified nutrients, metals and metalloid, microplastics, fecal sterols, and Polycyclic Aromatic Hydrocarbons (PAHs) in both water and sediment samples. We also used isotopic tracing on macroalgae to identify the origin of organic matter and characterized benthic and fish communities, and algae biomass at each site. Pollution was more pronounced in the multiple-use area but also affected no-take areas. Effluents from wastewater treatment plants did not meet legislative standards, and reefs in the multiple-use area were enriched in orthophosphate and ammonia compared to those in the no-take area. Nitrogen isotopes in macroalgae revealed sewage-derived nitrogen throughout the multiple-use area. Nutrient enriched sites exhibited higher abundances of fast-growing and opportunistic green macroalgae, and higher biomass of brown macroalgae. The port area, within the multiple-use area, showed high PAHs, coprostanol and metal(loid) concentrations, suggesting untreated sewage and nautical chemical pollution. Microplastics were widespread in sediment and water samples. We documented the pervasive impacts of marine pollution on reef habitats even within marine protected areas in oceanic regions, demonstrating that local pollution control, sewage management and regulating procedures in port areas are critical to protect marine ecosystems. Comparisons with previous studies suggest marine pollution has substantially increased in the Archipelago in the last ten years. This is the first comprehensive assessment of marine pollution in an oceanic environment in Southwestern Atlantic, showing these isolated environments are not immune to pollution impacts.
Keywords: Benthic communities; Fernando de Noronha; Nutrient; Reef; Sewage; Stable isotopes; Wastewater infrastructure